Implementation of the Eco-Industrial Park Model in the Context of Environmental Protection of the Agglomeration (On the Example of the Lviv Agglomeration) - Zhabynets Olha Yo.; Banakh Oleksandra I. (Bìznes Inform, 2025)
The article is dedicated to the study of the prospects for the implementation and development of eco-industrial parks in the Lviv agglomeration in the context of environmental protection. The results of the first phase of activities aimed at implementing the eco-industrial park model in Ukraine within the framework of the international project GEIPP – Ukraine (the UNIDO program «Global Program for Eco-Industrial Parks in Ukraine: Implementation at the Local Level») have been analyzed. It is noted that the experience of implementing eco-industrial parks in developing countries and countries with transitional economies indicates that access to funding is a key problem for the realization of eco-industrial park initiatives. The dynamics of main environmental indicators of the Lviv region have been analyzed. It is found established that the current situation in the natural ecosystem of the region is deteriorating: the volume of circulating and successively (repeatedly) used water is decreasing; the water ecosystem is in a threatening state due to significant discharges of polluted wastewater into surface water bodies; the share of Lviv Oblast in emissions of pollutants and carbon dioxide from stationary sources of pollution at the national level has reached critically high levels, particularly in the first year of the full-scale war makes 6.41% for pollutant emissions and 4.68% for carbon dioxide emissions, which are the highest figures in the last 10 years. It is argued that the reported statistical indicators should be considered for situational assessment of the starting conditions when implementing the principles of a circular economy and creating an effective system for environmental protection in the Lviv agglomeration. An assessment of the budget expenditures of the communities in the Lviv agglomeration for environmental protection in 2023 was conducted. It is concluded that nearly 90% of the agglomeration’s expenditures on environmental protection were made by only 4 communities (Davydiv, Solonka, Pustomyty, and Lviv). It is pointed out that the Lviv community, which has the highest concentration of manufacturing enterprises and serves as the core of the agglomeration, is among the three communities with the lowest indicators of the share of environmental protection expenditures in the community’s budget and the expenditures per manufacturing enterprise. It is further concluded that there is a need to establish an effective system for environmental protection in the Lviv agglomeration and to transition to a circular economy, which should become the main incentives for implementing the eco-industrial park model in the agglomeration area.